Proportion of severity of retinal hard exudates and its association with systemic risk factors - Silpa, Devi; Sathar, Anuja; Thankappan, Beena (International Journal of Advances in Medicine, 2020)
Background: Diabetic macular edema (DME) characterized by deposition of hard exudates in central retina is now the leading cause of visual loss in persons with diabetes mellitus. Several studies have shown association between severity of retinal hard exudates and various components of serum lipid. The aim of this study is to estimate the proportion of severity of retinal hard exudates with risk factors like dyslipidemia, duration of diabetes, hypertension, HbA1c levels and microalbuminuria. Methods: A hospital based cross sectional study was done involving 242 diabetic retinopathy patients. After dilated fundus examination, severity of retinal hard exudates was graded by photographs with Topcon fundus camera using modified airlie house classification. These grades were divided into three groups. Group 1 (absent or minimal hard exudates) included patients with grade 0, 1 or 2 hard exudates; group 2 (hard exudates present), included patients with grade 3 or 4 hard exudates and group 3 (prominent hard exudates), patients with grade 5 hard exudates. Values of serum lipid profile, HbA1C and urine microalbumin were analysed in association with severity of retinal hard exudates. Results: Out of the 242 diabetic retinopathy patients, the male female ratio was 1:1 and the mean age was 59.8±7.4 years. There were 12% patients in group one, 52.5% in group two and 35.5% in group three. On univariate analysis, severity of hard exudates was significantly associated with serum cholesterol (p value<0.01), LDL (p value<0.01) triglycerides (p value<0.01), HbA1c (p value<0.01), systemic hypertension (p value<0.01) and urine microalbumin (p value=0.01). Conclusions: Severity of retinal hard exudates in diabetic retinopathy patients is significantly associated with risk factors like systemic hypertension, dyslipidemia, raised HbA1C levels and urine microalbumin.